ANALISIS SEKTOR-SEKTOR PEMBENTUK PDRB DAN PENENTUAN SEKTOR UNGGULAN DI WILAYAH KABUPATEN KEBUMEN - Ratnasari, Emma Dwi (P4M STIE Putra Bangsa, 2014)
This study aims to analyze the forming of GRDP sectors in Kebumen, and determine which sectors are priorities to be developed in order to encourage economic growth Kebumen. The research uses descriptive analytical method, the data used are secondary data in the form of time series of GDP Kebumen and Central Java Province with the observation year 2005 to 2009. The analysis used is the analysis of LQ (Location Quotient), shift share, Typology Klassen, Model Growth Ratio (MRP), and Overlay. Results Analysis of Location Quotient (LQ) shows the basic sector in Kebumen is Mining and Quarrying sector, Agricultural sector, services sector and financial sector, Rental and Service, no visible shift of economic structure, where the primary sector is still a focus for regional income, Overlay analysis produced 5 seed sector, the Mining and Quarrying Sector, Agricultural Sector, Industry Sector, Finance, Ownership, and Corporate Services and Services, Klassen Typology analysis showed that the Mining and Quarrying sector and the services sector is a sector advanced and rapidly growing sector, Agriculture and Financial sectors, Renting and Business Services is an advanced but depressed sector, Manufacturing sector is a potential sectors / could still be developed, the analysis of the leading sectors that need to be developed namely Services sector. Based on the analysis in this study, several suggestions can be presented as follows: Kebumen district must give priority to the services sector with a competitive advantage as well as specialization without having to neglect other sectors. Need to develop co-operation of Agriculture, Industry and Services are intensive and sustainable.